PENGADAAN BAHAN PUSTAKA PADA PERPUSTAKAAN FAKULTAS SYARIAH UIN IMAM BONJOL PADANG - Murnahayati Murnahayati (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2018)
Abstract: Procurement of library materials is a series of development policies. Library collection. All of the final collection development policies are procurement of library materials. Procurement collection is the process of collecting library material that will be used as a library collection. Collections held by a library should be relevant to their interests and needs, complete and up to date, so as not to disappoint the service community. In providing various types of library materials needed by users, libraries often experience problems or constraints. These constraints can be seen from the limited funds owned by the library, collection selection, utilization of the collection and so on. For this reason, in the case of library materials procurement, the library must be thorough and careful so that the available funds can be used as well as possible and the benefits can be felt by the library user. Procurement policy depends on several things including: budget, objectives and priorities of the organization, types of users and needs, relations with other libraries and languages. There are several things that need to be considered in formulating collection development policies, among others: Institution programs, user needs, collection types, library criteria, number of copies, and languages.Keywords: Collection procurement, Higher education library.Abstrak : Pengadaan bahan pustaka merupakan rangkaian dari kebijakan pengembangan. Koleksi perpustakaan. Semua kebijakan pengembangan koleksi akhir muaranya adalah pengadaan bahan pustaka.  Pengadaan koleksi adalah proses menghimpun bahan pustaka yang akan dijadikan koleksi perpustakaan. Koleksi yang diadakan oleh suatu perpustakaan hendaknya relevan dengan minat dan kebutuhan, lengkap dan terbitan mutakhir, agar tidak mengecewakan masyarakat yang dilayanani.  Dalam menyediakan berbagai jenis koleksi bahan pustaka yang dibutuhkan pengguna, perpustakaan sering mengalami masalah atau kendala. Kendala tersebut dapat dilihat dari keterbatasan dana yang dimiliki oleh perpustaakn, pemilihan koleksi, pemanfaatan koleksi dan sebagaianya. Untuk itu, dalam hal pengadaan  bahan pustaka , perpustakaan harus teliti dan cermat agar dana yang ada dapat dipergunakan sebaik-baiknya dan dapat dirasakan manfaatnya bagi perngguna perpustakaan Kebijakan pengadaan tergantung pada beberapa hal antara lain: anggaran, tujuan dan prioritas dari organisasi, jenis pemakai dan kebutuhannya, hubungan dengan perpustakaan lain dan bahasa. Ada beberapa hal yang perlu di pertimbangkan dalam merumuskan kebijakan pengembangan koleksi antara lain: Program lembaga, Kebutuhan pengguna, Jenis koleksi, Kriteria pustaka, Jumlah eksemplar, dan Bahasa.Kata Kunci : Penggadaan koleksi,  Perpustakaan perguruan tinggi.